Structural and magnetic properties of disordered crystalline Fe50Mn25+xSn25?x alloys with x =-1.25, 0.0, 2.5, 5.0, 7.5 - Pachín W. (2021)
Disordered crystalline Fe50Mn25+xSn25?x alloys, with x =-1.25, 0.0, 2.5, 5.0, 7.5 (close to the full-Heusler alloys), were arc-melted in a high purity argon atmosphere and the molten pellets were individually sealed in quartz tubes also under argon atmosphere. Subsequently, they were annealed at 1173 K for 4 days, being finally quenched in a bath with cold water. Structural and magnetic properties have systematically been studied using X-ray diffraction,57Fe, and119Sn Mössbauer spectroscopies, and magnetization measurements recorded at room temperature. Rietveld refinement of the X-ray diffraction patterns of the annealed samples with x =-1.25 and 0 has revealed the presence of two hexagonal crystallographic phases: (i) a chemically disordered solid solution identified as ??(Fe/Mn)3Sn (majority fraction) and (ii) the ??Fe5Sn3 intermetallic compound (minority fraction). For samples with x = 2.5, 5.0, and 7.5, the Rietveld analysis has only indicated the presence of a chemically disordered solid solution identified as ??(Fe/Mn)3(Sn/Fe/Mn). Although compositions of the Fe50Mn25+xSn25?x alloys are close to that of full-Heusler alloys, none of them has the expected L21 structure. The average crystallite sizes, estimated from the Williamson-Hall method, are in the range of 256-62 nm. The average sizes has gradually decreased as the x-content is increased. Mössbauer results have shown localized-type magnetism from Fe non-equivalent sites, and itinerant-like magnetism on119Sn-probes. Magnetic hysteresis loops, recorded at 300 K for a maximum field of 2200 Oe, have indicated that the remanent and coercive fields have systematically decreased as the x-parameter has increased. Coercive fields are in the range for soft magnets (1-20 Oe). © 2021, Universidad Nacional de Colombia. All rights reserved.